The development of Adolescent Career Resilience Scale (ACRS): A Rasch model analysis - Afiati, Evi; Faturohman, Nandang; Saripudin, Mohamad (Universitas Negeri Padang, 2022)
Career resilience plays a central role in individual career development and can make individuals find their attitudes, behaviors, and actions that are appropriate to changing situations. The high and low career resilience also affects the individual's career success. Career resilience has been essential to developing since adolescence, but there has been no instrument development to explore adolescent career resilience. This study aims to develop the Adolescent Career Resilience Scale (ACRS) using the Rasch model analysis. The research uses a quantitative approach. Determination of research participants using a convenience sampling method. The participants in this study were 312 students (104 junior high school students, 104 senior high school students, and 104 vocational students in Banten province) involved in the empirical test. ACRS has an item reliability value of 0.97 in the Special category and personal reliability of 0.70 in the good category. Cronbach's Alpha value is 0.78 with a good category. The results of ACRS analysis using the Rasch model produce 31 items that can be used to reveal adolescent career resilience.